Genetic structure and diversity of the amphitropical disjunct grass Leptochloa crinita (formerly Trichloris crinita) and implications for restoration - Quiroga, Raul Emiliano; Mathiasen, Paula; Quiroga, M. Paula; Fernandez, Roberto J.; Díaz, Dayana G.; Premoli, Andrea Cecilia (Asociación Argentina de Ecología, 2025)
Amphitropical species have disjunct distributions south and north of the equator. That is the case of Leptochloa crinita, a perennial grass found in dry and warm regions of South and North America, and recommended for rangeland restoration. We analyzed to what degree the distribution of the species in both subcontinents shaped its genetic differentiation and population variability. We collected seeds from 15 populations from South America and 7 from North America, and grew them in a common garden to evaluate adaptive variation. Three microsatellite markers and DNA sequences from one nuclear (ITS1-5.8S-ITS2) and one chloroplast region (rpl32-trnL) were used to analyze recent and historical gene flow, respectively. We used climatic niche models to infer past suitable habitats. We found significant genetic variability among populations within each subcontinent, but low genetic differences between populations from South vs. North America; these were detected only with microsatellites and not with DNA sequences. Results show that the species has diverged from a common gene pool in the recent past (~500-3300 generations ago [estimate: ~3000-20000 years]). Populations from South America had plants with more and taller inflorescences, more tillers and heavier seeds than the North American ones, which could represent adaptations to the less stressful environments that the species inhabits in South America. Climatic niche models indicate few potential habitats for the species in North America during the Last Glacial Maximum and Middle Holocene, in contrast to South America, where potential habitats seemed to be comparable or more extensive than at present. This and previous studies provide a view of the genetic resources of the species. Results suggest that —if necessary, and taking proper precautions— the admixture of L. crinita populations or the germplasm translocation between subcontinents are alternatives to consider in restoration practices.